Efek Perlokusi dari Tindak Tutur Komisif pada Drama Boku no Satsui ga Koi wo Shita - Ni Komang Ari Kurnia; Pradhana Ngurah Indra; Sari Ida Ayu Laksmita (Japanology: The Journal of Japanese Studies, 2025)
Abstract This research is entitled "Perlocutionary Effects of Commissive Speech Act in Drama Boku no Satsui ga Koi wo Shita”. This study aims to analyze how the function of commissive speech act such as promising, refusing, threatening and offering are used by speakers, the form of locution uttered by the speaker, the illocutionary meaning contained in the speech, and how the use of these functions affects the attitudes, actions, and responses of the interlocutor in interactions between characters. This study uses a qualitative descriptive method with a listening and note-taking technique in data collection. The theories used include the speech act theory by Austin (1962), the classification of commissive speech act by Yule (1996), and the perlocutionary effect theory by Kartika (2014). The results of the study showed that there were 11 commissive speech act data consisting of four functions, namely promising (3 instances), refusing (1 instance), threatening (6 instances), and offering (1 instance). The threatening function is the most dominant, while the refusing and offering functions appear the least. The perlocutionary effects that arise vary, with more positive responses found in the promising, threatening, and offering functions, while the refusing function tends to cause negative reactions. This study shows that commissive speech acts are not only used to convey the speaker's commitment, but also impact diverse perlocutions of the interlocutor. Keywords: commissive speech act, Japanese drama, perlocutionary effects, speech acts.